Highly efficient sulfimidation of 1,3-dithianes by Cu(I) complexes - Giribabu, Lingamallu; Singh, Surya P.; Patil, Nandkumar M.; Kantam, M. Lakshmi; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synthetic Communications, 2008)
A series of four Cu(I) complexes were tested for sulfimidation of 1,3-dithianes in the presence of [N-(p-tolysulfonyl)imino]phenyliodinane (PhI = NTs) as the nitrene-transfer agent. Cu(TMPhen)(PPh3)Br is an efficient catalyst with more than 90% yield of the corresponding product with less reaction time as compared to the literature copper(I) complexes.
Keywords: 1; 3-dithianes; Cu(I) complexes; PhI = NTs; sulfimidation

Highly selective synthesis of mono-ethylene glycol phenyl ethers via hydroxyalkoxylation of phenols by cyclic carbonates using large pore zeolites - Kinage, Anil K.; Gupte, Sunil P.; Chaturvedi, Rajiv K.; Chaudhari, Raghunath V. (Catalysis Communications, 2008)
Hydroxyalkoxylation of phenols by cyclic carbonates catalyzed by alkali loaded large pore zeolites has been reported. The study shows that KL type zeolite was recyclable and selective in producing mono-ethylene glycol pheryl ethers in similar to 98.5% yield. Various substituted simple phenols were converted into mono-ethylene glycol ether of phenols with over 90% yields, except 3-bromo and 2-methyl phenols. Mono hydroxyl plienols such as hydroquinone, biphenol and BPA (2,2-bis(4-hydroxyphenyl)propane) also produce corresponding mono- and di-ethylene glycol ethers. The ratio of ethylene carbonate to phenol was found to be critical for selective formation of monoethylene glycol phenyl ether of phenols. A ratio of two results in formation of appreciable amount of diether derivative viz., 2-(2-phenoxyethoxy) ethanol. Compared to ethylene carbonate, a lower reactivity of 1,2-propane carbonate was found for hydroxyalkoxylation of phenol. It was found that ring opening at less hindered methylene carbon of 1,2-propylene carbonate prevailed giving rise to selective formation of beta-hydroxy phenyl ethers. The reactivity of ethylene carbonate towards O-alkylation versus transesterification of phenol has been explained on the basis of HSAB concept. Finally, it has been shown that yield of mono-ethylene glycol phenyl ether is controlled both by basicity and channel architecture of zeolite structure. KL zeolite was found to be the most effective zeolite because of it's intermediate basicity and one dimensional channel architect. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cyclic carbonate; ethylene glycol phenyl ether; hydroxyalkoxylation; phenol

Heterogenized copper catalysts for the amination of arylhalide: synthesis, characterization and catalytic applications - Patil, Nandkumar M.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Applied Catalysis A-General, 2010)
This research investigated the synthesis, characterization and catalytic activity of heterogenized copper complexes for the selective amination of aryl halides. Amination reactions using homogeneous copper catalyst systems are not generally selective and it is also difficult to recover the catalyst from the homogeneous system for recycling. To overcome these difficulties, our efforts were directed towards the development of cheaper heterogeneous catalyst systems, which can be easily recovered and recycled. Heterogenized analogs of the homogenous Cu complexes were prepared using two methods: (a) encapsulation of copper complexes in zeolite-Y and (b) tethering of copper complexes on various supports like zeolite-Y, silica, charcoal, or clay. The encapsulated and tethered copper catalysts on zeolite-Y were characterized using EPR, Diffused reflectance UV-vis, XRD, IAS, ICPES, SEM, and TEM. The results confirmed that the copper complexes were truly heterogenized in zeolite-Y support. Encapsulated and tethered copper complexes were tested for amination of aryl iodide. The effects of various reaction parameters were examined using tethered Cu(Phen)(PPh(3))Br-PTA-Y catalyst to determine optimum conditions. A recycle study of encapsulated and tethered Cu catalyst was carried out to test their robustness for possible commercial exploitation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amination; C-N coupling; Copper; heterogeneous catalysis; mesoporous materials